Design of Infusion Schemes for Neuroreceptor Imaging: Application to [11C]Flumazenil-PET Steady-State Study. (31st March 2016) - Feng, Ling; Svarer, Claus; Madsen, Karine; Ziebell, Morten; Dyssegaard, Agnete; Ettrup, Anders; Hansen, Hanne Demant; Lehel, Szabolcs; Yndgaard, Stig; Paulson, Olaf Bjarne; Knudsen, Gitte Moos; Pinborg, Lars Hageman
Abstract : This study aims at developing a simulation system that predicts the optimal study design for attaining tracer steady-state conditions in brain and blood rapidly. Tracer kinetics was determined from bolus studies and used to construct the system. Subsequently, the system was used to design inputs for bolus infusion (BI) or programmed infusion (PI) experiments. Steady-state quantitative measurements can be made with one short scan and venous blood samples. The G A B A A receptor ligand [C 11 ]Flumazenil (FMZ) was chosen for this purpose, as it lacks a suitable reference region. Methods . Five bolus [C 11 ]FMZ-PET scans were conducted, based on which population-based PI and BI schemes were designed and tested in five additional healthy subjects. The design of a PI was assisted by an offline feedback controller. Results . The system could reproduce the measurements in blood and brain. With PI, [C 11 ]FMZ steady state was attained within 40 min, which was 8 min earlier than the optimal BI (B/I ratio = 55 min). Conclusions . The system can design both BI and PI schemes to attain steady state rapidly. For example, subjects can be [C 11 ]FMZ-PET scanned after 40 min of tracer infusion for 40 min with venous sampling and a straight-forward quantification. This simulation toolbox is available for other PET-tracers.